ABC is a triangle in which angle abc <90 and ADperpendicular to BC. prove that AC square= AB square + BC square - 2 BC× BD
Attachments:
![](https://hi-static.z-dn.net/files/d34/cc7382b4e8d1d4ad16dc292fba19cee8.jpg)
………(i)
Again,ADB is a right triangle, right angled at D, therefore, by Pythagoras theorem,


– 2BC.BD
– 2DB.BC
– 2DB.BC
Answers
Answered by
1
Answer:check below
Step-by-step explanation:
Attachments:
![](https://hi-static.z-dn.net/files/d34/84730841fbf7740b92c7fa21c40d6e3e.jpg)
Answered by
2
Hope You Liked it..
Mark as Brainiest...
Follow me for more doubt solving..
Mark as Brainiest...
Follow me for more doubt solving..
Attachments:
![](https://hi-static.z-dn.net/files/de0/e53e9fa21e9f2069de3f147540ac568e.jpg)
Similar questions
AB2=AD2+BD2AB2=AD2+BD2 …….. (1)
In triangle ADC;
AC2=AD2+DC2AC2=AD2+DC2
Or, AC2=AD2+(BC–BD)2AC2=AD2+(BC–BD)2
=AD2+BD2+BC2–2BC.BD=AD2+BD2+BC2–2BC.BD……… (2)
Substituting the value of AB2 from equation (1) in equation (2), we get;
AC2=AB2+BC2–2BC.BDAC2=AB2+BC2–2BC.BDproved